The study of the influence of the types of electrode covers on hydrogen diffusion and root crack during arc welding using covered electrodes - Yumurtaci, S; Gultekin, N (NATL INST STANDARDS (NIS) OFF CONF & SCI PUBL, 2001)
As known, apart from various gases, an important amount of hydrogen is absorbed by weld pool during arc welding. Hydrogen has a special importance in resulting different types of failures during welding. One of the most important effects in occurring of hydrogen is covered electrodes. The electrodes ready-for-use are affected by both the storing environments and the special disturbing effects in workshop and consumption field. For the cover of electrode, the outwearing effect is the moisture in air. As known covered electrode has a hydroscopic property. Therefore, during the production of covered electrode the moisture ratio can be raised to high values. In welding process the hydrogen atoms can decrease their diameter up to 0.62 Angstrom; therefore they can be easily diffused. Hence, it is obvious that since the root pass of weld seam with two or more passes is subjected to high degrees of temperatures for a long period, the hydrogen atoms can be diffused to that root pass. In this work, the time-depended changes and the effects on root crack of hydrogen for different types of electrodes are investigated by using an experiment installation equipped according to DIN8572.
Keywords: diffusible hydrogen; rutile electrode; solubility; Instruments & Instrumentation